The relationship between algebraic thinking and geometric thinking among second-grade intermediate students - Al-Harbi, Abdullah Thuwaini; Aldalean, Bader Muhammed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the level of algebraic thinking, and geometric thinking, and to determine the relationship between algebraic thinking and geometric thinking among students of the second intermediate grade, The study followed the descriptive correlative approach, The study community consisted of students of the second intermediate grade in Al-Dawadmi Governorate, and their number was approximately (650) students, The study sample included (172) students, and the algebraic thinking test and the geometric thinking test were used by the researcher. and the results reached the following: - The overall degree of algebraic thinking and its skills was high, with the exception of the skill of logical reasoning to address or solve problems, which came to a medium degree.- The overall degree of engineering thinking and its skills came to a medium degree.- There is a partial correlation that is not statistically significant at the level of significance (0.05), between the algebraic thinking skills and the levels of geometrical thinking, except for the relationship between the skill (the skill of understanding and using algebraic structures and variables) and the level of (generalization), which is statistically significant at the level of significance (0.05) There is a positive, statistically significant correlation (0.05) between the students' total scores in the algebraic thinking test, and the students' total scores in choosing geometric thinking among second-grade intermediate students.
Keywords: algebraic thinking; geometric thinking; second intermediate grade